Anesthesia-free procedures for benign prostate obstruction. Issue 1 (January 2015) - Ebbing, Jan; Bachmann, Alexander
<x xml:space="preserve">Abstract</x> Purpose of review Perhaps, 30% of patients with benign prostate obstruction experience no symptom relief with drug therapy, necessitating surgical intervention. General anesthesia can be too dangerous for elderly or frail men, making local anesthesia desirable. Such minimally invasive procedures may offer time-saving, effective, gentle, and well tolerated alternatives. Recent findings Recent interest has focused on the mechanical devices and intraprostatic injections. The commercially available UroLift system demonstrates promising short-term data in randomized multicenter trials. Rezum steam injection therapy is intriguing, although currently study-based with limited data. NX1207 and PRX302 are new intraprostatic injection drugs demonstrating interesting results in phase I and II studies, whereas conflicting results surround the prostatic injection of botulinum toxin A. For transurethral microwave therapy, definitive evaluations regarding the treatment of chronic urinary retention in nonsurgical patients are ongoing. Summary Although none of these minimally invasive procedures must be performed under general anesthesia, all require local anesthesia with possible sedation. In most studies, pain therapy management is rudimentary or not described. Although good short-term results are described, no long-term data are available.